Screening of Streptococcus suis in swine workers of selected states in Peninsular Malaysia - Lee, Chee Yien; Zakaria, Zunita; Selvarajah, Gayathri Thevi; Mustaffa-Kamal, Farina; Voon, Kenny Gah Leong; Fong, Michelle Wai Cheng; Ooi, Peck Toung (Veterinary World, 2024)
Background and Aim: Streptococcus suis is a zoonotic pathogen that is highly associated with contact between live pigs and raw pig material. In view of the recent reports of human infections in Malaysia, epidemiological data on the status of S. suis in the human population, especially among people working closely with pigs and/or raw pork, should be provided. The aim of this study was to detect S. suis among individuals working in the swine industry in several major pig production areas in Peninsular Malaysia. Materials and Methods: Demographic information, exposure determinants, and oral swabs were collected from swine personnel, including farmers, butchers, and veterinarians. Oral swabs were subjected to bacterial isolation and conventional polymerase chain reaction (PCR) assays for S. suis detection. Results: The study included 40 participants working in the swine industry, with a predominant representation of males (62.5) and Malaysian Chinese individuals (60.0) who consumed pork (92.5). Notably, none of the participants reported consuming raw or partially cooked pork. In spite of their occupational exposure risk, none of the oral swabs showed positive results for S. suis infection. Conclusion: To the best of our knowledge, this is the first report and detection study of S. suis using oral swabs obtained from swine personnel in Peninsular Malaysia. © 2024 Veterinary World.